2015
DOI: 10.1177/0093854815613103
|View full text |Cite
|
Sign up to set email alerts
|

Stigma, Pluralistic Ignorance, and Attitudes Toward Seeking Mental Health Services Among Police Officers

Abstract: Due to the stressors inherent in the law enforcement profession, police officers may be at increased risk for a variety of personal and mental health-related concerns. Despite these tendencies, officers have historically refrained from seeking psychological services. Several factors have been identified to explain their hesitance, including public stigma and self-stigma regarding mental health issues. In this study, sworn police officers in Texas and Oklahoma completed a 62-item online survey related to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
111
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(124 citation statements)
references
References 131 publications
(352 reference statements)
8
111
1
1
Order By: Relevance
“…Participants were able to recall R2MR components 12 months after training. On the self-report measures, participants did not report significant changes in mental health symptoms, resilience, or work engagement, but did report small increases in mental health knowledge and small temporary decreases in stigma; in contrast, the open-ended participant responses indicated that most found the training helpful for increasing mental health awareness, understanding, and communication skills, as well as helping to reduce stigma by correcting erroneous beliefs about mental health and perceptions of consequences for accessing mental health care (Karaffa & Koch, 2016), which may increase help seeking. In this context, researching the R2MR program delivered by MHCC, which is a brief intervention using cognitive behavioral therapy style skills developed for a broad audience, has provided important results; nevertheless, PSP researchers and trainers should explore the contemporary DND adaptation of R2MR, as well as continue pursuing opportunities to improve evidence-informed cognitive behavioral therapy style training programs, intervention programs, and implementation processes in support of PSP resilience and mental health.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…Participants were able to recall R2MR components 12 months after training. On the self-report measures, participants did not report significant changes in mental health symptoms, resilience, or work engagement, but did report small increases in mental health knowledge and small temporary decreases in stigma; in contrast, the open-ended participant responses indicated that most found the training helpful for increasing mental health awareness, understanding, and communication skills, as well as helping to reduce stigma by correcting erroneous beliefs about mental health and perceptions of consequences for accessing mental health care (Karaffa & Koch, 2016), which may increase help seeking. In this context, researching the R2MR program delivered by MHCC, which is a brief intervention using cognitive behavioral therapy style skills developed for a broad audience, has provided important results; nevertheless, PSP researchers and trainers should explore the contemporary DND adaptation of R2MR, as well as continue pursuing opportunities to improve evidence-informed cognitive behavioral therapy style training programs, intervention programs, and implementation processes in support of PSP resilience and mental health.…”
Section: Resultsmentioning
confidence: 84%
“…Concerns about stigma and possible identifiability may also have impacted participant reports (e.g. Halpern, Gurevich, Schwartz, & Brazeau, 2009;Henderson, Van Hasselt, Leduc, & Couwels, 2016;Karaffa & Koch, 2016). Relatedly, in the absence of diagnostic interviews assessments of symptoms and skills, as well as absent assessment of objective behavioral indicators, the current results may not replicate and may not reflect the full impact of the training program.…”
Section: Limitationsmentioning
confidence: 86%
See 3 more Smart Citations